VD_FINDINFO Arrêt / 2016 / 982 vom 28. November 2016 - VD Tribunal cantonal (2016)
ACCIDENT, INVALIDITÉ PARTIELLE, FORCE PROBANTE, RAPPORT MÉDICAL, ÉVALUATION DE L'INVALIDITÉ | 28 LAI, 28a LAI, 29 al. 1 LAI, 4 LAI, 16 LPGA, 6 LPGA, 61 LPGA, 7 LPGA, 8 LPGA